Anisotropic nanoporous morphology of ZnO-supported Co that enhances catalytic activity. Issue 17 (22nd April 2021) - Coaty, Christopher M.; Corrao, Adam A.; Petrova, Victoria; Kim, Taewoo; Fenning, David P.; Khalifah, Peter G.; Liu, Ping
Abstract : Conversion reaction synthesis methods yield a nanoporous ZnO-supported Co catalyst with an anisotropic crystal structure and an anisotropic, hierarchical, columnar wall morphology that is highly efficient for steam reforming of ethanol to produce H2 . Abstract : A novel conversion reaction synthesis (CRS) method is used to synthesize ZnO-supported Co nanoporous metal hybrid structures from a co-precipitated nanocomposite precursor of ZnO and Co3 O4 . After removal of Li2 O with water, the resulting material consists of ZnO-supported Co nanoparticles that are interconnected to form anisotropic micro-particles. Additionally, individual ZnO nanoparticles have an anisotropic morphology, as revealed by synchrotron XRD analysis. Microscopy and surface area studies show these materials have an average pore size of 10–30 nm and specific surface areas up to 28 m 2 g −1 . The hybrid structure also has increased heat resistance compared to that of pure nanoporous metals; the Co phase within the ZnO–Co hybrid exhibits much less coarsening than the analogous nanoporous metal without ZnO at temperatures of 400 °C and above. These ZnO–Co hybrid materials were tested as heterogeneous catalysts for the steam reformation of ethanol at 400 °C. The nanoporous ZnO–Co hybrid material exhibits complete conversion of ethanol and high hydrogen selectivity, producing H2 with a molar yield of approximately 70%.